Frequency of use of body ornaments and motivations of students to use oral piercing - Nieto Murillo, Eugenia; Cerezo Correa, María del Pilar; Cifuentes Aguirre, Olga Lucía (Universidad y Salud, 2012)
Objective: To determine the frequency of body adornments and the motivations of students for having oral piercings. Methodology: Mixed method. Descriptive transversal study, qualitative grounded theory. Population: School children from three institutions in Manizales. Sample: 1053 students. Unit of analysis: reasons for having oral piercings. Unit of work: Experiences of students who have oral piercings. The technique of discussion group was used to collect qualitative information. Results: 19.7% have oral piercings, more than half are women. Most of them have been pierced by themselves or by a friend. The motivations for these piercings have as a common factor the response of the students to adult dispositions regarding their everyday world. Conclusions: The use of oral piercing is a frequent practice that may become a public health problem. The motivations of the students to have piercing are related to aesthetics, self-affirmation and eroticism.